PATHOMORPHOLOGY OF THE ADRENAL GLANDS IN DAMAGED BY MAGNESIUM CHLORATE EXPOSURE - Nordjigitov Azamat Musakulovych (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
A single administration of the defoliant leads to structural, hemodynamic disturbances and dystrophic changes in the cells of the cortex and medulla of the organ. The relative weight of the adrenal glands is significantly increased compared to the control. An expansion of the relative width of the adrenal cortex and its zones is noted. The volume of nuclei of cortical and chromaffin cells is significantly increased compared to the control. The vascular reaction is manifested not only in hyperemia, but also in local hemorrhages. Karyopyknosis is determined in cortical cells, vacuolization of their cytoplasm. After a single introduction of the pesticide, there is a decrease in the synthetic processes of the secretory cycle in the cells of the cortical substance zones, and a decrease in the amount of lipids and ascorbic acid indicate an increase in the phase of hormone secretion from cortical cells. With a single exposure to a pesticide at a dose of 1/10 LD50, there is a sharp increase in the morphofunctional activity of the adrenal glands along with the development of reactive-destructive changes in it against the background of disruption of synthetic processes in cells.